2016
DOI: 10.21859/jgn.3.1.38
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of self medication and related factors in older people in Kermanshah in 2014

Abstract: Introduction and purpose: Self-medication is a common phenomenon which frequently happening among elderly. The goal of this study was to investigate self medication and associated factors among elderly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The self-medication sub-category indicates that the older people, in some cases, take new blood pressure medications without consulting a doctor or take non-medical advice more than that of the doctors (Chang, 2015). In Mexico, a study indicated that 50 percent of the older people take medicines arbitrary (Balbuena et al, 2009), while in Iran it was about 90 percent (Korani et al 2016). In Iran, medications for reducing blood pressure are the most commonly used drug group.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…The self-medication sub-category indicates that the older people, in some cases, take new blood pressure medications without consulting a doctor or take non-medical advice more than that of the doctors (Chang, 2015). In Mexico, a study indicated that 50 percent of the older people take medicines arbitrary (Balbuena et al, 2009), while in Iran it was about 90 percent (Korani et al 2016). In Iran, medications for reducing blood pressure are the most commonly used drug group.…”
Section: Concluding Discussionmentioning
confidence: 99%